2023
DOI: 10.26668/businessreview/2023.v8i2.1017
|View full text |Cite
|
Sign up to set email alerts
|

The Economarketing Model: Development of Productive and Sustainable Tourism Area

Abstract: Purpose:  The purpose of this study is to examine the effect of green marketing on the tourist intention to avoid future damage to the "Lingkar Selorejo" tourism area, which is supposed to be developed by the Malang Regency government.   Theoretical framework: The examination of Lingkar Selorejo as a green marketing rural tourism village comprises of identification of local potential, resources, social and local community insight. Thereafter, determining an appropriate green marketing model as a concept. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…9 Secondly, to validate consistency of their judgment on the goal of SCT. 10 The respondent consisted: Staff of Department of Culture-Tourism, Tourism Ministry staff, Central Bureau -Statistics, the Development Planning Agency at Sub-National Level, and Non-Governmental Organizations (NGOs). Besides, Tour Operator, Foreign tourists and tourists, Hotel -Restaurant Association, Tours and Travel Agencies, Coastal community leaders, Craftsmen, and a number of local communities included.…”
Section: Methodsmentioning
confidence: 99%
“…9 Secondly, to validate consistency of their judgment on the goal of SCT. 10 The respondent consisted: Staff of Department of Culture-Tourism, Tourism Ministry staff, Central Bureau -Statistics, the Development Planning Agency at Sub-National Level, and Non-Governmental Organizations (NGOs). Besides, Tour Operator, Foreign tourists and tourists, Hotel -Restaurant Association, Tours and Travel Agencies, Coastal community leaders, Craftsmen, and a number of local communities included.…”
Section: Methodsmentioning
confidence: 99%
“…These include a lack of awareness or misinformation about sustainable energy options, perceived inconvenience or high upfront costs of green technologies, and skepticism towards corporate greenwashing. Overcoming these barriers requires transparent, credible, and engaging marketing strategies that address consumer concerns and highlight the tangible benefits of sustainable energy choices [181][182][183] . Tailoring marketing strategies to different consumer segments based on their preferences, behaviors, and demographic characteristics can enhance the effectiveness of sustainable energy marketing.…”
Section: Sustainable Marketing Practices Of Energy Companiesmentioning
confidence: 99%
“…Research by Sulaiman et al (2019) showed the potential and benefits of an area that can be used for educational tourism and tourist visits for educational activities, training, empowerment programs, research, laboratory studies, and higher education programs. Educational tourism programs have been shown to help students learn better and get along better with others (Husin et al, 2022;Agustina et al, 2023). With 39.2 million elementary schools to high school students in Indonesia, the future of educational tourism based on school students is expected to be even brighter.…”
Section: Introductionmentioning
confidence: 99%